Women feeding cities: Mainstreaming gender in urban agriculture and food security - Hovorka, A.; Zeeuw, Henk de; Njenga, M. (CTA / Practical Action, 2009)
This book seeks to draw our attention to the role of women – especially low-income women – in food production and to provide development workers with the tools to ensure that gender is prioritised in food security initiatives. Part I focuses on gender in agriculture and features case-studies from around the world. Part II provides guidelines for gender mainstreaming in urban agriculture projects.